Effect of pressure-assisted thermal annealing on the optical properties of ZnO thin films - Berger, Danielle; Kubaski, Evaldo Toniolo; Sequinel, Thiago; Da Silva, Renata Martins; Tebcherani, Sergio Mazurek; Varela, José Arana [UNESP] (Wiley, 2012)
ZnO thin films were prepared by the polymeric precursor method. The films were deposited on silicon substrates using the spin-coating technique, and were annealed at 330°C for 32h under pressure-assisted thermal annealing and under ambient pressure. Their structural and optical properties were characterized, and the phases formed were identified by X-ray diffraction. No secondary phase was detected. The ZnO thin films were also characterized by field-emission scanning electron microscopy, Fourier transform infrared spectroscopy, photoluminescence and ultraviolet emission intensity measurements. The effect of pressure on these thin films modifies the active defects that cause the recombination of deep level states located inside the band gap that emit yellow-green (575nm) and orange (645nm) photoluminescence. © 2012 John Wiley & Sons, Ltd.
Keywords: Photoluminescence; Pressure treatment; ZnO thin film